Effect of Educational Program on Doctors' Knowledge and Practice of Oxygen Therapy (Medical Forum Monthly, 2023)
Objective: To investigate the effect of an educational program about oxygen therapy on the doctors' knowledge and doctors' practice.Study Design: Cross-sectional, quasi-experimental research studyPlace and Duration of Study: This study was conducted at the Pediatric Emergency Department of Nishtar Hospital, Multan from September 2022 to October 2022.Materials and Methods: Overall, 266 doctors were included in our study, both sexes. The program was delivered in the emergency department of the pediatric unit. The pre-test and post-test approach was used to evaluate the effectiveness of the structured educational program. The independent variable was the educational program, while the dependent variable was the doctor’s knowledge and practice about oxygen toxicity. Data analysis was performed using SPSS version 23. Data was tabulated as mean ± SD for numerical values and frequency percentages for categorical values. T-test and chi-square test were applied to see the association among variables.Results: The average test scores before and after the implementation of educational program was 10.99±2.77 and 18.15±1.41, respectively. The average test score of post-test versus pre-test was greater and the difference was statistically significant, (p<0.001). The mean post test score of male and female doctors was 18.02±1.51 and 18.37±1.15, respectively. The difference was statistically insignificant, (p<0.050).Conclusion: Regular practical and educational training sessions are necessary for doctors to stay updated on the latest guidelines for oxygen therapy. This will enable them to provide the best possible care to patients who require oxygen therapy.